Rapid Transformational Therapy (RTT): An Emerging Non-invasive Therapeutic Modality - Raveendran, Savitha; Kaliaperumal, Chandrasekaran (Biology, Engineering, Medicine and Science Reports)
We write to highlight an emerging non-invasive therapeutic option that can be potentially used for various medical ailments. RTT is Rapid Transformational Therapy, a hybrid therapy developed by Marisa Peer in England, UK.1 It combines the best principles of hypnotherapy, cognitive behavioural therapy (CBT), Neuro- Linguistic Programming that offers fast effective results for a range of psychological, psychiatric and physical conditions. As opposed to traditional therapies, RTT is a solution-focussed treatment offering rapid, effective and long-lasting change usually within one (or within three maximum) session. RTT embraces the positive aspects of all the above techniques that are known to produce a transformative effect on the clients. Hypnotherapy uses trance, regression and hypnotic conditioning. RTT goes beyond this process, Marisa identified that regardless of their issue, in sessions clients benefitted from her applying a particular set of techniques over and over again. These insights provided the foundations for RTT to emerge as a distinctive approach.